Topics of Animal and Human Respiratory System of the Fifth Grade Elementary Schools Developed Through Pop-Up Book Media - Putra, Komang Triana Tantra; Parmiti, Desak Putu (Journal of Education Technology, 2020)
The implementation of this research was based on the problems encountered because the material in students’ books was still less extensive in the limitation of examples and explanations on the students’ books in one subject matter on the topic of animal and human respiratory system. This research aimed to develop Pop-Up book media on the topic of animal and human respiratory system. In addition, the results of the interviews showed that the use of media in learning was deficient. This research was carried out by using ADDIE model which was consisted of five phases, namely: (1) analysis, (2) design, (3) development, (4) implementation, and (5) evaluation. However, in this research the implementation and evaluation phases were not carried out due to time limitations, costs, and resources. The subject of this research was the Pop-Up book media. The object of this research was the validity of the Pop-Up book media. The data collection method was a questionnaire. The rating scale instrument was used in the form of validation assessment sheets to measure the validity of Pop-Up book. Data validity was analysed by using the mean formula to find out the average score of media validity. This research produced a Pop-Up book on the topic of animal and human respiratory systems with an average score of 4.56 which was categorized into very good category. It meant that Pop-Up book media was suitable to be used. It was a solution to the problem and could be used by teachers in delivering some materials.